Radar Clutter Suppression Solution Based on ICA - Luo Qian (2013 Fourth International Conference on Intelligent Systems Design and Engineering Applications, 2013)
It has been a hard task in radar signal processing to detect dim moving targets in a very strong clutter background. This paper presents a new radar clutter suppression solution based on independent component analysis technique to estimate independent components (signals) and separate clutter signal from the observed low signal to noise ratio radar echo. The problems of the sequence order ambiguity and sign uncertainty encountered in the practical use of independent component analysis for signal component separation have been solved by applying kurtosis criterion to separate basis signals. Simulation results show that this method can efficiently suppress strong clutter and detect dim moving target signals.